Utopia, Arcadia and the Forest of Arden - Paterson, Ronan (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
In Utopia (1516) Thomas More created a humorous world with a serious purpose. His invented republic was a place where existing conventions and structures did not exist, allowing the positing of alternatives. The creation of alternative worlds which satirise or critique contemporary society is a technique employed by writers in most genres, in most periods and in most cultures. More’s work is interesting for us in this context at least in part because of the likelihood that Shakespeare was familiar with it. When he created The Forest of Arden in As You Like It, for some of the characters there are utopian elements in their experience of that place. But Arden is not only a putative Utopia. Arden also contains elements of the pastoral Arcadia, again drawing upon ancient precedents, but more recently explored by English poets Edmund Spenser in The Shepherd’s Calendar (1579) and Philip Sidney in The Countess of Pembroke’s Arcadia (1593). This article interrogates the use of Utopian and Arcadian elements in the creation of one of Shakespeare’s most complicated plays. Like More’s Utopia its intention is comic. Like Sidney’s poem it is romantic, but unlike both of them it is ultimately about returning to a real world, with new perceptions of who we are, not as a society but as individuals.